O nó entre o espaço e o tempo em Santa Tereza: os bares na paisagem boêmia em um bairro de Belo Horizonte - Maria Leticia Silva Ticle (2016)
The bohemian Santa Tereza neighborhood in Belo Horizonte led to the production of this Masters thesis. The research took place in order to understand what works as ballast for this attribute of the neighborhood, which path led to the bohemian image of Santa Tereza, and to what extent bohemia may be, in fact, a relevant argument for the neighborhood to be considered cultural heritage within the city. Here they are presented, the history of the neighborhood, the discussion of the notion of bohemia and its meaning in Santa Tereza. The concepts of landscape and gentrification were articulated to the discussion of bohemia and heritage, pointing risks and potentialities of this association. The Masters thesis is the result of a bibliographical and documental research in institutional and personal archives in the city of Belo Horizonte, and the production of sources through interviews, conversations and participant observations.